Studi Literatur: Manfaat Cream Topical Extract Hylocereus Polyrhizus 7,5 % pada Penyembuhan Luka - Sriwahyuni Sriwahyuni; Takdir Tahir; Yuliana Syam (Jurnal Kesehatan Manarang, 2018)
Wound healing is a complex physiological response from living systems for physical, chemical, mechanical or thermal injury, where cells and matrix components act in rhythm to facilitate wound regeneration and restore tissue integrity. The skin is a complex organ consisting of the epidermis, dermis, and complementary skin, including hair follicles and sebaceous glands besides that the skin is also known as the largest organ in the body and plays several important roles ranging from regulating temperature, preventing infection and also a very dynamic organ which continually replaces cells, the depth of damage to the skin, both superficial and partial, can affect the length and amount of use of wound dressing material so that wound healing requires an appropriate environment and skill ability in selecting topical dressings to improve the healing process that is suitable for each type wounds, the right and innovative healing stage is estimated to heal within 2-8 weeks. This literature study aims to determine the benefits of topical cream extract of hylocereus polyrhizus 7.5% on wound healing. Search was done using pubMed, cochrane, google scholar and secondary search data published from 1990 to 2017. 7.5% red dragon fruit (EBNM) contains antioxidants, flavonoid phlyphenols which can increase collagen synthesis in wound healing besides seeds dragon fruit is able to relieve flasks and keep the skin moisture smooth due to the content of linoleic acid. Every 1 gram of Red Dragon Fruit contains 8.3 mg of total flavonoids and 10.8 mg of total phenol. Red Dragon Fruit (BNM) with high fiber, low in calories, and rich in antioxidants. Red Dragon Fruit Extract (EBNM) 7.5% is better at repairing granulation tissue and epithelial tissue, so it has the potential to be used as a wound healing therapy.